Four New Cases of SLC35A2-CDG With Novel Mutations and Clinical Features - Abuduxikuer, Kuerbanjiang; Wang, Jian-She (Frontiers in Genetics, 2021)
SLC35A2-CDG is a rare type of X-linked CDG with more than 60 reported cases. We retrospectively analyzed clinical phenotypes and SLC35A2 genotypes of four cases of SLC35A2-CDG from four unrelated families of Han ethnicity in China. All patients had infantile onset epilepsies that were completely or partly resistant to multiple anti-epileptic medications or ketogenic diet. Three patients had severe developmental delay. All patients were female patients carrying de novo deleterious mutations in SLC35A2 (NM_001042498.2) gene, including one canonical splice-site mutation (c.426+1G>A), one large deletion (c.-322_c.274+1del), and two frameshift mutations leading to premature stop codon (c.781delC/p.Arg289ValfsTer88 and c.601delG/p.Ala201GlnfsTer148). Novel clinical features in some of our patients include anemia, hypertriglyceridemia, hypertonia, small ears, extra folds on earlobes, and maternal oligohydramnios or hypothyroidism during pregnancy. In one patient, concomitant Marfan syndrome was confirmed for having positive family history, carrying a heterozygous known disease-causing mutation in FBN1 gene (c.7240C>T/p.Arg2414Ter), and presence of typical features (rachnodactyly, ventrical septal defect, and mitral valve regurgitation). In conclusion, we expanded clinical phenotype and genetic mutation spectrum of SLC35A2-CDG by reporting four new cases with novel pathogenic variants and novel clinical features.